Future land use simulation modeling for sustainable urban development under the shared socioeconomic pathways in West African megacities: insights from Greater Accra Region - Siabi, E. K.; Kabo-bah, A. T.; Anornu, G.; Akpoti, Komlavi; Mortey, E. M.; Incoom, A. B. M.; Yeboah, K. A. (Elsevier, 2025)
The study explores the evolving land use patterns and their implications for sustainable development in Ghana and neighboring megacities. Using 15 years of historical Land Use and Land Cover (LULC) data combined with Land-Use Harmonization datasets, the study applies the Future Land Use Simulation (FLUS) model to project future LULC dynamics under Shared Socioeconomic Pathway (SSP) scenarios in the densely urbanized Greater Accra Region (GAR) of West Africa. Analyzing historical and current land use dynamics in the GAR revealed notable shifts, notably a decrease in Rangeland and an increase in Built-up areas. Future projections of LULC under SSP scenarios show continuous expansion of Built-up areas, particularly under SSP245 (middle of the road scenario) and SSP370 (Regional Rivalry scenario). This is consistent with results from the urban growth analysis using Urban Expansion Intensity Index (UEII), indicating high-speed expansion in baseline periods and shifts towards medium to high-speed expansion under SSP245 and SSP370 with low-speed expansion under the SSP126 (Sustainability scenario). Shannon entropy analysis shows dispersed urban sprawl, especially under SSP245 and SSP370, with rapid increases in Built-up areas and declines in green areas. For instance, the analysis of the landscape metrics reveal that built-up and green areas are projected to increase and decrease up to 87% and 12% respectively, under these scenarios. The decline in urban green areas was significantly influenced by proximity to the central business district (CBD), with green spaces diminishing more as distance to the CBD decreased. Therefore, relevant local legislation, such as the 2016 Land Use and Spatial Planning Act (Act 925) must be enforced, along with integrating urban initiatives and policies that promote green areas, is essential for ensuring the sustainability of urban ecosystems for the well-being of both humans and the environment. This enables West Africa to achieve its Global commitments as reflected in the UN SDGs, towards the New Urban Agenda (NUA) and the Africa Urban Agenda 2063.